Serum factors modify the cellular requirement for Ca2+, K+, Mg2+, phosphate ions, and 2-oxocarboxylic acids for multiplication of normal human fibroblasts. - McKeehan, W L (1980)
The rate of multiplication of a population of cultured human lung fibroblasts is determined by the level of common nutrients and serum factors in the medium. By application of the principles of Henri--Michaelis--Menten kinetic analysis to cell growth in vitro, the relationship between the level of a macromolecular fraction of serum that contains growth factors and the concentration of individual nutrient that is required to support a half-maximal rate of cell multiplication was explored. The requirement for the majority of individual nutrients is independent of the level of serum factors in the medium. This includes all 20 amino acids, glucose, purines, pyrimidines, polyamines, choline, and inositol. In contrast, serum factors determine the cellular requirement for Ca2+, K+, Mg2+, Pi, and 2-oxocarboxylic acids. These nutrients are most likely involved in cellular processes related to the mechanism by which growth factors in serum control the cell multiplication rate.